Symposium 5: Embedding Networked Learning in Greek Higher Education Institutions: Policy and Practice: Symposium Introduction - Stamatis, Demosthenes; Kargidis, Theodoros (Proceedings of the International Conference on Networked Learning, 2008)
The Operational Programme for Education and Initial Vocational Training (O.P. "Education") is a framework programme designed to aid Greece in meeting the challenges arising internationally due to the development of innovative technologies.(http://www.epeaek.gr). It is co-financed by the European Social Fund (ESF), the European Regional Development Fund (ERDF) and the Ministry of National Education. Having as a target to enhance the quality of education provided at all levels, the O.P. "Education" has funded a number of actions with the aim of raising the effectiveness and competitiveness of the existing system of Higher Education in Greece. Crucial among them was the action supporting the introduction and use of Information and Communication Technologies (ICTs) in the graduate and postgraduate study programmes (curricula) of Higher Education Institutions. This action is underway and is planned to finish by the end of 2008. In this context most of the Greek Institutions are incorporating Networked Learning techniques (both synchronous and asynchronous) in their study programmes. The symposium has the goal of acting as a forum for the exchange of knowledge and experiences, gained in this process of introducing Networked Learning in Greek Higher Education Institutions, and to discuss policy and practice issues. The papers of the symposium focus on a number of such issues regarding organizational, pedagogical, and technological aspects of Networked Learning: Sgouropoulou C., et. al. present a framework that has been established to support the combinatory use of distance learning techniques and multimedia-enhanced instructional content for the support of IT Curricula in Greek Technological Educational Institutes. They also present their evaluation results. Vassilakis, Psaroudakis and Kalogiannakis analyze the use of an asynchronous education platform at Technological Educational Institute (TEI) of Crete, focusing on aspects regarding teacher-student relations. Kabouridis G. presents an assessment of the influences and the consequences that networked learning techniques brought in the learning and working environment of the department Mechanical engineering, TEI of Patras and discuses the mutual impact of educational and technological issues. Triantis D., Stavrakas I.,.et al., present a virtual laboratory environment which was developed in order to teach physics of semiconductors, in a blended learning approach. This symposium was organised within the activities of the Project "Undergraduate Studies of the Technological Educational Institute of Thessaloniki/ Work Package 1" , funded in the context of the Priority Action Line 2: "Promotion and improvement of education and vocational training in the framework of lifelong learning" (EPEAEK, Action category 2.2.2.a.) of the Operational Program for Education and Initial Vocational Training.